CoOx thin film deposited by CVD as efficient water oxidation catalyst: change of oxidation state in XPS and its correlation to electrochemical activity. Issue 16 (22nd December 2015) - Weidler, Natascha; Paulus, Sarina; Schuch, Jona; Klett, Joachim; Hoch, Sascha; Stenner, Patrick; Maljusch, Artjom; Brötz, Joachim; Wittich, Carolin; Kaiser, Bernhard; Jaegermann, Wolfram
Abstract : To reduce energy losses in water electrolysers a fundamental understanding of the water oxidation reaction steps is necessary to design efficient oxygen evolution catalysts. Abstract : To reduce energy losses in water electrolysers a fundamental understanding of the water oxidation reaction steps is necessary to design efficient oxygen evolution catalysts. Here we present CoO x /Ti electrocatalytic films deposited by thermal and plasma enhanced chemical vapor deposition (CVD) onto titanium substrates. We report electrochemical (EC), photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) measurements. The electrochemical behavior of the samples was correlated with the chemical and electronic structure by recording XPS spectra before and after each electrochemical treatment (conditioning and cyclovoltammetry). The results show that the electrochemical behavior of CoO x /Ti strongly depends on the resulting electronic structure and composition. The thermal deposition leads to the formation of a pure Co(ii )O x which transforms to a mixed Co(ii )Co(iii )O x during the OER. This change in oxidation state is coupled with a decrease in overpotential from η = 0.57 V to η = 0.43 V at 5 mA cm −2 . Plasma deposition in oxygen leads to a Co(iii )-dominated mixed CoO x, that has a lower onset potential as deposited due to a higher Co(iii ) content in the initial deposited material. After the OER XPS results of the CoO x /Ti indicate a partial formation of hydroxides and oxyhydroxides on the oxide surface. Finally the plasma deposition in air, results in a CoO x OH2 surface, that is able to completely oxidizes during OER to an oxyhydroxide Co(iii )OOH. With the in situ formed CoOOH we present a highly active catalyst for the OER ( η = 0.34 at 5 mA cm −2 ; η = 0.37 V at 10 mA cm −2 ).